Fluorescence-Guided Surgery and Fluorescence Laparoscopy for Gastrointestinal Cancers in Clinically-Relevant Mouse Models - Cristina A. Metildi; Robert M. Hoffman; Michael Bouvet (Gastroenterology Research and Practice)
There are many challenges that face surgeons when attempting curative resection for gastrointestinal cancers. The ability to properly delineate tumor margins for complete resection is of utmost importance in achieving cure and giving the patient the best chance of prolonged survival. Targeted tumor imaging techniques have gained significant interest in recent years to enable better identification of tumor lesions to improve diagnosis and treatment of cancer from preoperative staging modalities to optimizing the surgeon’s ability to visualize tumor margins at the initial operation. Using unique characteristics of the tumor to fluorescently label the tissue can delineate tumor margins from normal surrounding tissue, allowing improved precision of surgical resection. In this paper, different methods of fluorescently labeling native tumor are discussed as well as the development of fluorescence laparoscopy and the potential role for fluorescence-guided surgery in the treatment of gastrointestinal cancers.